Developmental, Reproduction, and Feeding Preferences of the Sitobion avenae Mediated by Soil Silicon Application - Xiaoru Wang; Weiwei Li; Jia Yan; Yi Wang; Xingyan Zhang; Xiaoling Tan; Julian Chen (Plants, 2023)
Silicon occupies an important position in the nutrient requirements of wheat. It has been reported that silicon enhances plant resistance to phytophagous insects. However, only limited research has been carried out on the effects of silicon application to wheat and Sitobion avenae populations. In this study, three silicon fertilizer concentrations were treated for potted wheat seedlings, including 0 g/L, 1 g/L, and 2 g/L of water-soluble silicon fertilizer solution. The effect of silicon application on the developmental period, longevity, reproduction, wing pattern differentiation, and other vital life table parameters of the S. avenae were determined. The cage method and the Petri dish isolated leaf method were used to determine the effect of silicon application on the feeding preference of the winged and wingless aphid. The results showed silicon application had no significant effect on the aphid instar of 1–4; although, 2 g/L silicon fertilizer prolonged the nymph stage and 1 and 2 g/L of silicon application all shortened the adult stage and reduced the longevity and fertility of the aphid. Two instances of silicon application reduced the net reproductive rate (R0), intrinsic rate of increase (rm), and finite rate of increase (λ) of the aphid. A 2 g/L silicon application prolonged the population doubling time (td), significantly reduced the mean generation time (T), and increased the proportion of winged aphids. The results also demonstrated that the selection ratio of winged aphids in wheat leaves treated with 1 g/L and 2 g/L silicon was reduced by 8.61% and 17.88%, respectively. The number of aphids on leaves treated with 2 g/L silicon was significantly reduced at 48 and 72 h of aphids released, and the application of silicon to wheat was detrimental to the feeding preference of S. avenae. Therefore, the application of silicon at 2 g/L to wheat has an inhibitory effect on the life parameters and feeding preference of S. avenae.